2020
DOI: 10.1097/corr.0000000000001335
|View full text |Cite
|
Sign up to set email alerts
|

Are the Lives of Animals Well-spent in Laboratory Science Research? A Study of Orthopaedic Animal Studies in Turkey

Abstract: Background As in all fields of medicine, animal studies are widely performed in orthopaedics and have increased in number over time. However, it is not clear to what extent these studies provide a basis for future research or advancements in clinical science. Concerns about the reliability and translational ability of animal studies have been reported, and major orthopaedic journals and organizations are encouraging the reduction of unnecessary experiments on animals. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…[ 5 , 8 ] Researchers are expected to perform all experimental applications in accordance with 3Rs principles and to take necessary measures for animals to prevent suffering, distress, and pain. [ 3 , 9 ] Whereas replacement and reduction principles can be controlled and modified by the supervision of ethical committee before the approval of the experimental study, among the 3Rs principles, refinement is the most ambiguous one and the least monitored rule. [ 5 ] Several authors have suggested adding an animal welfare section to the methods part of publications to ensure that the refinement rule of 3Rs principles has been properly applied.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…[ 5 , 8 ] Researchers are expected to perform all experimental applications in accordance with 3Rs principles and to take necessary measures for animals to prevent suffering, distress, and pain. [ 3 , 9 ] Whereas replacement and reduction principles can be controlled and modified by the supervision of ethical committee before the approval of the experimental study, among the 3Rs principles, refinement is the most ambiguous one and the least monitored rule. [ 5 ] Several authors have suggested adding an animal welfare section to the methods part of publications to ensure that the refinement rule of 3Rs principles has been properly applied.…”
mentioning
confidence: 99%
“…[ 24 ] Researchers are expected to comply with the ARRIVE criteria and make the necessary effort to publish the results of animal studies and, therefore, the lives of animals sacrificed in experimental studies are not wasted for nothing. [ 3 , 19 , 20 ] van der Worp et al[ 25 ] suggested that the only way to prevent the unreported data in animal studies was to have a central registry system for animal studies similarly to clinical trial registry systems.…”
mentioning
confidence: 99%
See 3 more Smart Citations